O corpo/corporeidade na Educação em tempo integral - Ciclo I - MAGRIN, Natália Papacídero (2016)
This work aims to analyze which perception teachers active in elementary school in Full Time Schools in the city of Franca / SP, have about the body. This is a research classified as qualitative, from exploratory and descriptive nature, based on the phenomenological approach for the interpretation of the educational phenomenon. In this study were subjects, 10 teachers of the 2nd year of elementary school, from Full Time state school. The questions were: "What is the body for you?", "How do you work the student´s body?" and "The work with the body of the student in the Full Time School should be different from the work in Part-time School? Yeah? No? Why?" The data were analyzed using the Technique Elaboration and Analysis of Meaning Units (MOREIRA, SIMÕES, PORTO, 2005). Categorical analysis made in the political-pedagogical projects of each participating school unit, complete this study. The body conception as "movement / life" stood out slightly on the others 30% or 3 teachers, followed by "Instrument / System", "Body" and "Set of organs" both with 2 teachers (20%) each and finally with only one mention (10%) we have, "Shelter of the Soul", "Health" and "Unit". For the work with the student´s body, we have 7 of the teachers (70%) only concerned with the intellect, excluding the body of the teaching-learning process, 3 (30%) working with "Movement / Coordination" and / or "Perception of self and space”, other 2 (20%) with " Music / Relaxation ". Besides these ones were detected other 4 units ("Ludic Activities", "With Respect", "Body Care" and "It is the duty of the elementary school Teacher") that´s represents 10% or a teacher for each. About the differences in working with the student´s body in full-time and part-time, 60% (6) judged to be necessary, justifying in 40% (4) cases by increasing school hours. The others 40% (4) does not judge to be necessary differences in work, stating should be equal to 20% (2) cases. About the political-pedagogical projects, in none were found references to the body / corporeity, your conception or handle. With the data analyzed, we identified the body predominantly in a utilitarian view, this being fragmented and seen as working parts, which works because of something or someone. The supremacy of the mind over the body is present in the professional practice of the teachers, paying attention only to the treatment of the head in their classrooms, leaving the body under the responsibility of the physical education teacher.